Comparison of Inacbgs, Hospital, Unit Cost Based on The Activity Based Costing Method Delivery at Class C Private Hospitals - Fahmi Azhari Basya; Arrozi Arrozi; Muhammad Natsir (Jurnal Health Sains, 2023)
The era of the National Health Insurance (JKN) made hospitals have to make efficiency in their services, one of which is childbirth. Payment of BPJS Kesehatan through INACBGS is deemed insufficient to cover the hospital's profit margin. Moreover, the INACBGS rates is currently a rates product issued in 2016. It makes hospitals have to make efficient service rates so that they can develop their service quality and sustain them. Dinda Hospital is a class C private hospital with a business focus and BPJS Kesehatan patient care and has excellence in maternal care. The unit cost calculation technique using the Activity Based Costing (ABC) technique can provide an overview of rates efficiency. The purpose of this study was to compare the differences of 3 hospital rates, INACBGS rates, and ABC rates for normal delivery and caesarean section. Research is comparative analytic with cross sectional design. The clinical pathway is used to calculate ABC rates. The sample used was 30 samples of BPJS class 1 patients from each action (normal delivery and caesarean section) and the three rates were compared, namely hospital rates, INACBGS rates, and ABC rates using t-test dependent. Showed a significant difference in rates (p <0.005) between the INACBGS rate and the hospital rate for normal delivery (mean INACBGS 2,227,700, mean rate rs 5,491,462) and Caesarean (mean INACBGS 6,965,200, mean rate of rs. 6,557,208). there was a significant difference (p <0.005) between the hospital rate and the ABC rate for normal delivery (mean ABC rate 2,206,588) and caesarean section (mean ABC rate 4,328,672). The caesarean section rate is more profitable than normal delivery. Efficiency is needed so that the hospital can develop better services in the future